Evaluation of tumour infiltrating lymphocytes in core needle biopsies and resected specimens of breast carcinoma (Journal of Pathology of Nepal, 2020)
Background: Tumour-infiltrating lymphocytes are important predictors of response to neoadjuvant therapy in breast cancer. It remains unclear whether Tumour infiltrating lymphocytes scores in core needle biopsies are closely representative of those in the whole tumour of surgically resected specimens.The study aims to evaluate the concordance between tumor-infiltrating lymphocytes scores of core needle biopsies and surgically resected specimens as per recommendations and to assess the reliability of tumor-infiltrating lymphocytes score in core needle biopsies.Materials and Methods: Retrospective study from January 2016 to March 2019 done in tertiary care hospital. Tumor-infiltrating lymphocytes scores were sub-classified as low (≤10%), intermediate (11–49%), and high (40-90%). Relevant statistical tests were used and reliability score was done by Fisher’s test.Results: The mean value of tumor-infiltrating lymphocytes in 34 cases was 27.03% in core needle biopsies and 34.6% in surgically resected specimens. High tumor-infiltrating lymphocytes score was seen in 8 (23.6%) and 11 (32.4%) cases and low to intermediate score was seen in 26 (76.4%) cases and 23 (67.6%) in core needle biopsies and surgically resected specimens respectively. Intermediate and high tumor-infiltrating lymphocytes categories in core needle biopsies accounted for good agreement with surgically resected specimens (60%-intermediate, 87.5 %-high). More than three cores had a better agreement.Conclusions: Tumor-infiltrating lymphocytes score in core needle biopsies is of reliable value in breast cancer. Discrepancies may occur in tumours with HER2neu phenotype, PR status, and younger age.